Cost-Effectiveness Analysis of Hepatic Arterial Infusion of FOLFOX Combined Sorafenib for Advanced Hepatocellular Carcinoma With Portal Vein Invasion - Li, Meiyue; Lin, Shen; Wilson, Leslie; Huang, Pinfang; Wang, Hang; Lai, Shubin; Dong, Liangliang; Xu, Xiongwei; Weng, Xiuhua (Frontiers in Oncology, 2021)
Background Hepatic arterial infusion (HAI) of oxaliplatin, leucovorin, and fluorouracil (FOLFOX) plus sorafenib has a more desirable effect versus sorafenib for hepatocellular carcinoma (HCC) patients with portal vein invasion. However, considering the high cost of hepatic arterial infusion of chemotherapy (HAIC), this study evaluated the cost-effectiveness of HAIC plus sorafenib (SoraHAIC) versus standard care for HCC patients from the Chinese health system perspective. Methods A Markov multi-state model was constructed to simulate the disease course and source consumption of SoraHAIC. Costs of primary therapeutic drugs were calculated based on the national bid price, and hepatic artery catheterization fee was collected from the Fujian Provincial Price Bureau. Clinical data, other costs, and utility values were extracted from references. Primary outcomes included life-years (LYs), quality-adjusted life years (QALYs) and incremental cost-effectiveness ratio (ICER). The robustness of model was verified by uncertainty sensitivity analyses. Results SoraHAIC gained 1.18 QALYs (1.68 LYs) at a cost of 65,254, while the effectiveness and cost of sorafenib were 0.52 QALYs (0.79 LYs) and 14,280, respectively. The ICER of SoraHAIC vs sorafenib was 77,132/QALY (57,153/LY). Parameter that most influenced the ICER was utility of PFS state. The probabilistic sensitivity analysis (PSA) showed that SoraHAIC was not cost-effective in the WTP threshold of 3*Gross Domestic Product (GDP) per capita of China (30,492/QALY). But about 38.8% of the simulations were favorable to SoraHAIC at the WTP threshold of 3*GDP per capita of Beijing (72,000/QALY). When 3*GDP per capita of Fujian (47,285/QALY) and Gansu Province (14,595/QALY) were used as WTP threshold, the acceptability of SoraHAIC was 0.3% and 0%, respectively. Conclusions The study results indicated that SoraHAIC was not cost-effective in medium-, and low-income regions of China. In developed areas of China (Beijing), there was a 38.8% probability that the SoraHAIC regimen would be cost-effective.